Comparative evaluation of matrix-assisted laser desorption ionisation-time of flight mass spectrometry and conventional phenotypic-based methods for identification of clinically important yeasts in a UK-based medical microbiology laboratory. Issue 12 (25th August 2015) - Fatania, Nita; Fraser, Mark; Savage, Mike; Hart, Jason; Abdolrasouli, Alireza
Abstract : Aims: Performance of matrix-assisted laser desorption ionisation-time of flight mass spectrometry (MALDI-TOF MS) was compared in a side-by side-analysis with conventional phenotypic methods currently in use in our laboratory for identification of yeasts in a routine diagnostic setting. Methods: A diverse collection of 200 clinically important yeasts (19 species, five genera) were identified by both methods using standard protocols. Discordant or unreliable identifications were resolved by sequencing of the internal transcribed spacer region of the rRNA gene. Results: MALDI-TOF and conventional methods were in agreement for 182 isolates (91%) with correct identification to species level. Eighteen discordant results (9%) were due to rarely encountered species, hence the difficulty in their identification using traditional phenotypic methods. Conclusions: MALDI-TOF MS enabled rapid, reliable and accurate identification of clinically important yeasts in a routine diagnostic microbiology laboratory. Isolates with rare, unusual or low probability identifications should be confirmed using robust molecular methods.